MENGATASI KEJENUHAN BELAJAR PENDIDIKAN AGAMA ISLAM MASA PANDEMI DENGAN KARTU KWARTET - SUMARTONO SUMARTONO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
Everyone knows that covid-19 pandemic has ruined barely all aspect human life, including education. It caused problems and barrier for teacher, students and parents in upholding teaching and learning process. Transformation and accelaration of learning become challenges for educational institution, especially teacher. This problem needs solution and innovative adjustment in the realization of Islamic Education learning process. By the implementation of continuing creative innovation learning media strategy will be found to accommodate boredom and laziness which may pop up during the learning process. The use of media is one of yhe key determining students learning process. During is pandemic covid-19 in the teaching of islamic subject, by chapter of estabblishing household, the teacher is grateful feeling that he succeeded and was able to fulfill the mandate transfering knowledge to students in accordance to the purpose of learning. The indicators are students enthusiast, spirit and enjoyment during the learning pprocess. The learning media used to anticipate the the boredom is kwartet card which high school students are keen on. This research is an innovative solution so that it becomes Best Practice in the teaching and learning process of islamic studies in class XII KP 1 (Twelve Nursing One). The purpose of this reseach is to figure out the effeckveness of learning media in dealing with students’s boredom while learning. The result of the research shows that the use of learning media of kwartet card motivates, boosts their spirit and shares them pleasure in response to the learning boredom. Automatically students embrace knowledge enhancement in the chapter of establishing household. Students score improvement from 65 in the pretest up to 82 in the post test is a significant success, which is about 26%. ABSTRAKKita ketahui bersama bahwasannya Covid-19 telah memporak-porandakan segala aspek kehidupan termasuk dunia pendidikan. Hal tersebut menimbulkan masalah dan hambatan bagi guru, peserta didik dan orang tua dalam dalam melaksanakan kegiatan pembelajaran. Transformasi dan akselarasi pembelajaran merupakan bagi lembaga pendidikan khususnya guru. Problematika tersebut memerlukan solusi dan pembenahan inovatif dalam proses pembelajaran Pendidikan Agama Islam yang realita. Dengan inovasi yang kreatif secara terus menerus akan menemukan strategi media yang akan digunakan untuk mengantisipasi rasa jenuh dan malas dalam pembelajaran. Strategi penggunaan media salah satu penentu keberhasilan belajar siswa. Pembelajaran PAI masa pandemi Covid-19 materi membangun mahligai rumah tangga, guru bersyukur merasa sukses dan mampu melaksanakan amanah pengetahuan kepada siswa sesuai tujuan pembelajaran. Indikasi keberhasilan yaitu antusias, semangat dan senangnya siswa dalam pembelajaran. Media pembelajaran yang digunakan untuk mengatasi kejenuhan yaitu main kartu kwartet yang merupakan kesenangan anak seusia SMA/SMK. Penelitian ini merupakan solusi inovatif sehingga menjadi Best Practice dalam pembelajaran PAI XII KP 1. Tujuan penelitian ini untuk mengetahui efektifitas media pembelajaran dalam mengatasi kejenuhan siswa dalam belajar. Hasil penelitian menunjukkan bahwa media pembelajaran kartu kwartet memberi motivasi, semangat dan penuh kegembiraan mengatasi rasa jenuh siswa dalam menerima pelajaran. Secara otomatis ada peningkatan pengetahuan siswa dalam materi membangun mahligai rumah tangga. Peningkatan pretest 65 menjadi 82 setelah postes merupakan keberhasilan yang sangat signifikan yaitu 26 %.